POST-HEALTH EVALUATION BUILDING LINES AND ADMINISTRATION DEPARTMENT OF EDUCATION TECHNIQUE BUILDING FACULTY OF ENGINEERING UNY - Bambang Sugestiyadi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
The study of the post occupancy evaluation of the lecturing and administrationbuildings of the Department of the Construction Engineering Teacher Training of the Faculty of Technique of Yogyakarta State University is limited at the indicative level of the lecturing and administration buildings. It aims at investigating the technical and functional aspects of the lecturing and administration rooms of the Department of the Construction Engineering Teacher Training of the Faculty of Technique ofYogyakarta State University. It is conducted in 5 months of the lecturing period 199912000, with the analysis unit of the Department of the Construction Engineering with all of its activity aspects. The observing focuses of the study are a) the technical aspect, including: 1) lighting, 2) ventilation, 3) security, 4)fire fighting, 5) maintenance; b) the functional aspect, including: 1) room organization, 2) room capacity, 3) circulation, 4) communication, 5) the possibility to change. The data is collected using interview, field observation and documentation. The content validity is tested on relational judgmental basis. The results of the study show that in almost 50% of the lecturing period of the odd semester of 1999/2000 the lecturing room capacity is